The Fundamentalist Views of Sheikh Ma'ruf al-Nawdhi Through his treatise The Ladder to Understanding the Fundamentals (The Agreed-Upon Proofs as a Model) - Al-Barzanji, L.Mahmoud Abdul Rahman Najm Al-Din (Sulaimani Journal for Humanities, 2024)
All praise is due to Allah, Lord of the Worlds, and peace and blessings be upon His trustworthy Messenger, our master Muhammad, sent as a bearer of glad tidings to the believers and a warner to the disbelievers, and whose law abrogates all previous laws and religions, and upon his pure and righteous family and his noble and blessed companions, a lasting peace and blessings until the Day of Judgment. To proceed: There is no doubt that among the greatest and most esteemed of the Islamic sciences, the most beneficial and the most abundant in blessings, is the science of the principles of jurisprudence (Usul al-Fiqh). It is the foundation of Islamic law, the origin to which every branch is referred, the pride of the Muslim intellect, and the basis of Islamic law, for it encompasses the rules, pillars, and proofs that guide the jurist, the mufti, and the judge, leading them on the straight and righteous path to arrive at sound judgments based on solid foundations. Therefore, it is essential for them to know it, be guided by it, and draw from its wellspring. In every era, Allah has raised up for this science a group of eminent scholars and a gathering of the most virtuous people of that time, who have excelled in its study, established its foundations, and left us an immense wealth and a great legacy. Among these eminent figures is the venerable Imam, Sheikh Ma'ruf al-Nawdhi (may God have mercy on him), a luminary of the thirteenth century AH and one of the leading scholars of Usul al-Fiqh (Islamic jurisprudence) in his time. He codified the foundations of this noble science in his magnificent poem, "Sullam al-Wusul ila Ma'rifat al-Usul" (The Ladder to Understanding the Principles of Jurisprudence). We have no doubt that such a figure deserves to be studied and researched, and his role in that era and the sources he left behind—sources that truly served as a radiant light illuminating the path and minds of students of knowledge in his time and to this day—must be clarified and explained. After the College of Islamic Sciences at the University of Sulaimani decided to hold a scholarly conference on Sheikh al-Nawdhi, I decided to participate by writing a research paper on his aforementioned poem. I chose a title for my research and named it "The Usul al-Fiqh Views of Sheikh Ma'ruf al-Nawdhi as Presented in His Poem 'Sullam al-Wusul ila Ma'rifat al-Usul' (The Agreed-Upon Proofs as a Model)."